COMPETENCY BASED ENGLISH TEACHING AND LEARNING - Husenova Kumush (American Journals Publishing, 2024)
Competency-based education has been gaining popularity as an approach to teaching and learning that focuses on developing skills and knowledge needed to succeed in the real world. English language teaching has also embraced this approach, as it seeks to prepare learners for the challenges of communication in a globalized world. This article discusses the concepts and principles of competency-based English language teaching and learning.
Keywords: Competency-based language learning, assessment, learner-cantered approach